#KaburAjaDulu: A Digital Manifestation of Indonesian Youth’s Response to Societal and Structural Crises - Ardianti, Ruth; Yunita Monique, Putri; Rahman Eka, Agus; Handayani Saharuddin, Sri; Latifah, Humairah (Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
This study examines the digital phenomenon of the hashtag #KaburAjaDulu (